Effectiveness of minimally invasive surgery using incomplete phalangeal osteotomy for symptomatic curly toe of adults with a trapezoidal phalanx: An observational study - Ramírez-Andrés, Leonor; Nieto-García, Eduardo; Nieto-González, Elena; López-Ejeda, Noemí; Ferrer-Torregrosa, Javier (Frontiers in Surgery, 2022)
Background and aims Digital deformity in flexion, varismus (external rotation), and adduction with the toe in both supraduction and infraduction are called clinocampodactyly or curly toe. All adult patients with symptoms and a diagnosis of semirigid/rigid curly toes underwent radiological examination to verify the presence of a trapezoidal phalanx. The purpose of this study was to quantitatively determine the degrees of improvement of a dysmetric phalanx after incomplete phalangeal osteotomy using minimally invasive surgery. The points of improvement were determined using the American Orthopedic Foot and Ankle Society (AOFAS) scale score. Methods Between May 2021 and June 2022, 30 patients diagnosed with curly toes underwent unicortical osteotomy of the affected phalanx. The convergence angle was measured and the AOFAS scale scores were compared. Results A total of 33 toes underwent surgery. The average reduction of the convergence angle was 9°. The average improvement in the AOFAS scale score was 53 points at 6 months and reached almost 90 points (89.9 ± 6.1 points). Conclusions Incomplete phalangeal osteotomy performed with minimally invasive surgery of the trapezoidal phalanges of curly toes of adults can improve alignment and AOFAS scale scores.